Diagnóstico diferencial das anemias microcíticas e hipocrômicas - Naoum, Paulo Cesar [UNESP] (My University, 2011)
The microcytic and hypochromic anemia are the results of several pathologic conditions. They are the most prevalent forms of anemia in the Brazilian population , and frequently the clinical diagnosis depends on the laboratorial analysis. In many cases it is necessary to use specific techniques to determine if this anemia is due to iron deficiency or different types of thalassemia. This article shows the main technical applications used for differential diagnosis of microcytic and hypochromic anemia.

As anemias microcíticas e hipocrômicas são resultantes de várias condições patológicas. Por serem as mais prevalentes na população brasileira, muitas vezes o diagnóstico clínico depende dos resultados das análises laboratoriais. Em muitos casos há necessidade da utilização de técnicas específicas para determinar se esta anemia se deve à deficiência de ferro ou aos diferentes tipos de talassemias. O presente trabalho mostra as principais aplicações técnicas no diagnóstico diferencial das anemias microcíticas e hipocrômicas.
Differential diagnosis of microcytic and hypochromic anemia
Keywords: anemia; deficiência de ferro; talassemia; anemia; iron defficience; thalassemia